Control of white spot lesion adjacent to orthodontic bracket with use of fluoride varnish or chlorhexidine gel - Restrepo, Manuel [UNESP]; Bussaneli, Diego Girotto [UNESP]; Jeremias, Fabiano [UNESP]; Cordeiro, Rita de Cássia Loiola [UNESP]; Magalhães, Ana Carolina; Spolidorio, Denise Madalena Palomari [UNESP]; Santos-Pinto, Lourdes [UNESP] (Wiley, 2015)
The aims of this study were to compare the effectiveness of fluoride varnish and chlorhexidine gel in controlling white spot lesions (WSLs) adjacent to orthodontic brackets and to compare the ability of Quantitative Light-Induced Fluorescence (QLF) to measure mineral uptake with that of transverse microradiography (TMR). Thirty premolars with artificially induced WSLs were randomly assigned to three groups: (1) two applications of 5% NaF-varnish (F), with one-week interval, (2) two applications of 2% chlorhexidine gel (CHX), with one-week interval, and (3) control (CO), no treatment. QLF was used to measure changes in fluorescence before and after caries induction, 1 week after each application and 1, 2, and 3 months after the last application of F or CHX. TMR was performed to quantify lesion depth and mineral content after caries induction to evaluate the effects of F, CHX, and CO 3 months after the last application of agents. The data were analyzed by repeated measures ANOVA and Tukey’s test. All treatments increased the mineral content during the experimental period; however, F induced faster remineralization than CHX. The correlation between QLF and TMR was significantly moderate. Two applications of fluoride varnish or 2% chlorhexidine gel at one-week intervals were effective in controlling WSLs.